Biobattery Development from Orange Peel Waste: A Comparative Study of Fresh and Dried Matrices - Sarinah Pakpahan; Lastri Ma'asra; Kesya Paputungan; Farrel Bassel; Siti Fauziah; Aswin (Politeknik ATK Yogyakarta, 2025)
This study investigates the electrochemical performance of a biobattery using orange peel extract as the electrolyte. Four experimental groups were evaluated using fresh and dried orange peel matrices combined with either distilled water or seawater. Open-circuit voltage (Voc), short-circuit current (Isc), and power density were measured. All instruments were calibrated prior to testing. The results show that citrus waste can generate measurable electrical energy, with Voc ranging from 0.83 V to 1.36 V and Isc ranging from 0.26 mA to 0.54 mA. Maximum power density achieved was 73 μW/cm². The findings demonstrate that orange-peel-derived electrolytes are promising sustainable alternatives for low-power applications.